2022
DOI: 10.1002/biot.202100489
|View full text |Cite
|
Sign up to set email alerts
|

A seasonal simulation approach for culture depth influence on the temperature for different characterized microalgae strains

Abstract: Irradiance and temperature are among the most important variables that affect microalgae growth, being both difficult to control in outdoor raceway reactors utilized for large-scale production of microalgae biomass. They are mainly a function of the location of the reactors, thus, producing certain strains of microalgae in inappropriate places conduces to the failure of the systems. To be able to determine important parameters of any microalgae strains on the performance of the culture, such as the influence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 52 publications
2
6
0
Order By: Relevance
“…[174] It was demonstrated that although several species of microalgae can tolerate high light intensity at constant temperature, heating to around 40C stops photosynthesis. [95] Further, in accordance with other studies, [52] application of mathematical modeling of photosynthesis at different temperatures and light intensities to seasonal temperature and light intensity data has demonstrated that short, 5 sm light pass increases the productivity twice in all analyzed species (C.vulgaris 2.1; N.gaditana 2.1x; S.almeriensis 2). [95] At the same time, longer light passes can be somewhat beneficial for growth in summer by controlling the temperature (C.vulgaris 1.05; N.gaditana 1.3x; S.almeriensis 1.15).…”
Section: Adaptation To Temperature and Other Environmental Factors In...supporting
confidence: 86%
See 3 more Smart Citations
“…[174] It was demonstrated that although several species of microalgae can tolerate high light intensity at constant temperature, heating to around 40C stops photosynthesis. [95] Further, in accordance with other studies, [52] application of mathematical modeling of photosynthesis at different temperatures and light intensities to seasonal temperature and light intensity data has demonstrated that short, 5 sm light pass increases the productivity twice in all analyzed species (C.vulgaris 2.1; N.gaditana 2.1x; S.almeriensis 2). [95] At the same time, longer light passes can be somewhat beneficial for growth in summer by controlling the temperature (C.vulgaris 1.05; N.gaditana 1.3x; S.almeriensis 1.15).…”
Section: Adaptation To Temperature and Other Environmental Factors In...supporting
confidence: 86%
“…[95] Further, in accordance with other studies, [52] application of mathematical modeling of photosynthesis at different temperatures and light intensities to seasonal temperature and light intensity data has demonstrated that short, 5 sm light pass increases the productivity twice in all analyzed species (C.vulgaris 2.1; N.gaditana 2.1x; S.almeriensis 2). [95] At the same time, longer light passes can be somewhat beneficial for growth in summer by controlling the temperature (C.vulgaris 1.05; N.gaditana 1.3x; S.almeriensis 1.15). [95] Thus, it is possible to predict optimal microalgae cultivation conditions for specific microalgae strain and seasonal light and temperature variations.…”
Section: Adaptation To Temperature and Other Environmental Factors In...supporting
confidence: 86%
See 2 more Smart Citations
“…Rodríguez-Miranda et al [ 97 ] developed a simulation-based methodology to establish the influence of season and culture depth on the one-year irradiance and temperature of the culture, determining the biomass productivity of different microalgae strains. It is expected that such methodology could be used as an easy-to-manage decision-making tool for the optimal design and operation of large-scale microalgae facilities of the most cultivated microalgae strains ( Spirulina platensis, Chlorella vulgaris, Nannochloropsis gaditana, Isochrysis galbana , and Scenedesmus almeriensis ).…”
Section: Production Of Microalgae Biomass Enriched In Carbohydratesmentioning
confidence: 99%